Effect of Driving Pressure-Oriented Ventilation on Patients Undergoing One-Lung Ventilation During Thoracic Surgery: A Systematic Review and Meta-Analysis - Li, Xuan; Xue, Wenqiang; Zhang, Qinyu; Zhu, Yuyang; Fang, Yu; Huang, Jie (Frontiers in Surgery, 2022)
Background Hypoxemia and fluctuations in respiratory mechanics parameters are common during one-lung ventilation (OLV) in thoracic surgery. Additionally, the incidence of postoperative pulmonary complications (PPCS) in thoracic surgery is higher than that in other surgeries. Previous studies have demonstrated that driving pressure-oriented ventilation can reduce both mortality in patients with acute respiratory distress syndrome (ARDS) and the incidence of PPCS in patients undergoing general anesthesia. Our aim was to determine whether driving pressure-oriented ventilation improves intraoperative physiology and outcomes in patients undergoing thoracic surgery. Methods We searched MEDLINE via PubMed, Embase, Cochrane, Web of Science, and ClinicalTrials.gov and performed a meta-analysis to compare the effects of driving pressure-oriented ventilation with other ventilation strategies on patients undergoing OLV. The primary outcome was the PaO2/FiO2 ratio (P/F ratio) during OLV. The secondary outcomes were the incidence of PPCS during follow-up, compliance of the respiratory system during OLV, and mean arterial pressure during OLV. Results This review included seven studies, with a total of 640 patients. The PaO2/FiO2 ratio was higher during OLV in the driving pressure-oriented ventilation group (mean difference [MD]: 44.96; 95% confidence interval [CI], 24.22–65.70.32; I2: 58%; P < 0.0001). The incidence of PPCS was lower (OR: 0.58; 95% CI, 0.34–0.99; I2: 0%; P = 0.04) and the compliance of the respiratory system was higher (MD: 6.15; 95% CI, 3.97–8.32; I2: 57%; P < 0.00001) in the driving pressure-oriented group during OLV. We did not find a significant difference in the mean arterial pressure between the two groups. Conclusion Driving pressure-oriented ventilation during OLV in patients undergoing thoracic surgery was associated with better perioperative oxygenation, fewer PPCS, and improved compliance of the respiratory system. Systematic Review Registration PROSPERO, identifier: CRD42021297063.